Uganda : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment provides a well-informed and objective assessment, a diagnosis of problems, advice on their resolution, and an indication of the level of financial accountability risk in Uganda.. The report is structured as follows. Although, Uganda has a relatively well established legal and institutional framework for public sector financial management and accountability that is underpinned by the Constitution 1995, the Public Finance Act 1964 and the Treasury Accounting Instructions (Part I 1991 and Part II 1968). Section 1 of the report suggests that the present framework requires updating and strengthening and recommendations have been included to address the identified deficiencies. Section 2 of the Report contains proposals for further enhancing the budget and expenditure control system. Many of the incidences reported by the Auditor General point towards fraud, embezzlement and a waste in the use of public resources that exemplify the risks in budget execution. It also appears that insufficient attention is paid by Accounting Officers to their fiduciary responsibilities, including follow up on audit findings. A further issue is the acute shortage of professionally qualified and experienced accountants. Recommendations (short, medium and long-term) for mitigating those high risks are presented in Section 3. Several proposals are postulated in Section 4 concerning improving oversight arrangements and include: an annual audit certificate should be issued by the AG on the Public Accounts in accordance with international auditing standards and as required by law (no certificate has been issued by the AG for either of the last 4 years); auditor independence and the rights of access to all public bodies for audit purposes; quality assurance considerations; clearing the backlog of audits of state enterprises, addressing identified control weaknesses and regularizing reported anomalies; and mobilizing resources to enable the oversight institutions to discharge their mandates. Measures to further strengthen financial accountability in the local governments, and to mitigate fiduciary risk, are submitted in Section 5. mobilizing resources to effectively implement the Government's Strategy Plan to fight corruption and build ethics and integrity in public office is discussed in Section 6. Section 7 tackles developing a Strategic Plan to build the future direction of the accountancy profession; and Section 8 details measures to complete the budget framework, enhance budget execution, improve domestic revenue mobilization, and make the budget process transparent, among other proposals.